Adoption of chilli Production Technology Among the chilli Growers in Sehore District of Madhya Pradesh (Indian Journal of Extension Education, 2015)
This study was conducted in Sehore district of Madhya Pradesh in the year of 2013-14. The study revealed that majority of the chilli growers had high adoption behaviour (46.08%) followed by medium level of adoption(36.42%) and low adoption behavior ( 17.50%) regarding overall recommended chilli production technology respectively. The study also revealed that the socio-economic factors had positive and significant influence on the adoption of chilli production technology, among the chilli growers .